Identifikasi Pemanfaatan Hutan Mangrove dan Dampaknya Terhadap Daerah Pesisir Di Pantai Muara Serdang, Kecamatan Pantai Labu, Kabupaten Deli Serdang, Sumatera Utara - Elfi Yulita; Meilinda Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Mangrove forest is a general term used to describe a variety of tropical coastal communities dominated by certain species of trees or shrubs that have the ability to grow in salty waters. The purpose of this study was to determine the utilization of mangrove forests and the impact of mangrove forests on coastal areas. The research method used in this writing is a qualitative method. The process of analysis, and data collection is carried out and obtained through interviews and direct observation. The results of the research obtained that the surrounding community utilizes mangroves to be used as processed various types of food and sold to visitors who come, with these results can improve the economy of the local community. The impacts of mangrove forests for coastal areas include preventing coastal erosion, being a soil catalyst from seawater, fisheries habitat, providing a broad economic impact, a source of animal feed, preventing global warming, a source of income for fishermen, maintaining water and air quality, developing tourism areas, providing a source of firewood, developing science, and maintaining climate and weather.